Towards a Non-human Speciophilosophy - Giannetto, Enrico (Wydział Filozoficzny UAM, 2020)
After the publication of Jaques Derrida’s book, L’animal que donc je suis, anti-speciesism has been looking for a theoretical foundation for its ethical content. In my opinion, the defect of all these philosophical perspectives is that they still reduce animals to objects of human philosophy. Here, I develop a new framework in which animals are considered as subjects of their own philosophy. In analogy to the concept of ethnophilosophy, the concept of speciophilosophy is here introduced (§ 1, §3). The different ways of thinking between humans and other animals are outlined, by explaining the difference between verbal reasoning and thinking through images (§ 2). Human philosophies are shown to be anthropocentric ideologies, related to carnivorism (§4, § 8). Subsequently, animal speciophilosophies are discussed (§6) and a dialogical symphilosophein (§ 5) among all living beings is proposed to be the extension of the so-called philosophy of dialogue. Finally, it is shown how this perspective was present in the original Christian ethics (§7, §9, § 10).
Keywords: animals; animal philosophy; modes of thought; philosophy of dialogue; anti-speciesist ethics; Christian ethics; reverence for life; Jacques Derrida